Foresight Studies in the Context of Innovation Policy of Ukraine in 2000s - Yegorov, I. (Наука та наукознавство, 2015)
Issues of science and technology forecasting in Ukraine are discussed in the broader context of innovation policy. A review of main tendencies in economic, R&D and innovation performance in the independent Ukraine is given. Contradictions of the State Innovation Policy in Ukraine are highlighted. Detailed review of the procedures involved in the two recent foresight programs in Ukraine (implemented in 2004 and in 2008–2011) is made. Main results of the recent foresight programs are summed up and the most important problems in foresight studies in Ukraine are outlined. It is emphasized that foresight activities in Ukraine were being implemented in conditions of very weak and incoherent innovation policy; responsibilities of the key actors were not well defined; they were used as a predominantly policy-informing tool; innovation policy building was based on normative considerations rather than on the analysis of future developments in technological and S&T areas. Статья посвящена проблемам научно-технологического прогнозирования в Украине в более широком контексте реализации инновационной политики. Представлен обзор основных тенденций экономической, научно-технологической и инновационной деятельности в независимой Украине. Показаны противоречия в инновационной политике Украины. Выполнен подробный анализ хода реализации двух форсайтных программ в Украине: 2004 года и 2008–2011 годов. Обобщены их основные результаты и определены наиболее важные проблемы в области прогнозных исследований в Украине. Подчеркнуто, что форсайтные работы в Украине реализовывались в условиях слабой и непоследовательной инновационной политики; были нечетко определены задачи их участников; они в основном использовались как информационный инструмент для политиков; инновационная политика в Украине формировалась преимущественно на нормативной основе, а не на результатах анализа будущих тенденций в научно-технологической и инновационной сфере. Стаття присвячена проблемам науково-технологічного прогнозування в Україні в більш широкому контексті реалізації інноваційної політики. Представлено огляд основних тенденцій економічної, науково-технологічної та інноваційної діяльності в незалежній Україні. Показано протиріччя інноваційної політики України. Виконано докладний аналіз ходу реалізації двох форсайтних програм в Україні: 2004 року та 2008–2011 років. Узагальнено їхні основні результати і визначено найбільш важливі проблеми в галузі прогнозних досліджень в Україні. Підкреслено, що форсайтні роботи в Україні реалізовувались в умовах слабкої та непослідовної інноваційної політики; було нечітко визначено завдання їхніх учасників; вони здебільшого використовувались як інформаційний інструмент для політиків; інноваційна політика в Україні формувалась переважно на нормативній основі, а не на результатах аналізу майбутніх тенденцій в науково-технологічній та інноваційній сфері.